The effectivity of sodium hypochlorite (5.25%), ethyl alcohol (70%), polyvinylpyrrolidone-iodine (10%), glutaraldehyde (2%), and benzalkonium chloride (1 750), in the sterilization of gutta percha cones - Garcia, Mary Rose; Tan, Mike.; Porter, Irene Grace (Adviser).
This study was conducted to compare the sterilizing effectivity of sodium hypochlorite (5.25%, Ethyl Alcohol (70%), Polyvinylpyrrolidone-Iodine (10%), Glutaraldehyde (2%), and Benzalkonium Chloride (1:750), against microorganisms which may be carried by un-sterilized gutta percha cones. New gutta percha cones were inoculated with test microorganisms and immersed in the test solutions for specific time intervals. The points were then removed from the solutions and cultured in BHI-broth for 2 days at 37 degrees C. Samples were then taken from each positive culture (test tubes which showed turbidity), and transfered onto agar plates and subsequently incubated for 2 days at 37 degrees C. The colonies were then transfered onto slides and viewed under the light microscope for identification and verification. Results were tabulated and analyzed. There was no significant difference in the effectivity of the said agents in sterilizing gutta percha cones.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Gutta percha cones -- Sterilization; Root canal filling materials